Drawing and images of design: representation and meaning - Magalhães, Graça Maria Alves dos Santos (2014)
This abstract is based on the research being conducted on the relationship between design and drawing, whose results have been presented at various congresses. The aim of the research is to clarify the intervention of drawing in design, by differentiating between “object” and “image” and between the “symbolic character” and the “form of representation” by demonstrating that the efficiency of the project is based on conflict generated by the act of drawing in itself. Based on the triangular classification of design as author-programme- technology and drawing as representation- classification-imagination, it can be argued that: the object’s identity arises from the confrontation between representation and the image, thus questioning its unity. In other words the way of representing the object through a technical mediation referring to an abstract concept (the act of drawing), of symbolic function, and of attributing meaning to the symbol, insofar as it refers to object. This paper intends to approach drawing as the language that makes the appearance of the images of design possible. The images of design function as double: _ object of representation whilst represented image (physical representation); _object of desire whilst promoter of a story of subjective experiences and emotional relationships. Examples will be given. We consider the specificity of drawing through two possibilities: _representation as the action of drawing in the object’s presence; _representation as the action of drawing in the object’s absence. Drawing as a instrument of the project participates in the duality of the images: as representation of the idea (concept) and as action that provokes the emergence of the object before an interested and desiring subject. However, under these conditions, drawing exists as an action that does not dilute itself in the representation, since object and image, as differentiated and implied entities, relate to each other. Drawing is the place where the object’s necessary differentiation and uncertainty manifest themselves.